A Historical Perspective on the Role of Functional Lines of Block in the Re‐entrant Circuit of Ventricular Tachycardia. Issue 5 (9th March 2016) - PROIETTI, RICCARDO; ROUX, JEAN‐FRANCOIS; VERMA, ATUL; ALTURKI, AHMED; BERNIER, MARTIN L.; ESSEBAG, VIDAL
Abstract : The ablation strategy for ventricular tachycardia (VT) rapidly evolved from an entrainment mapping approach for identification of the critical isthmus of the re‐entrant circuit during monomorphic VT, toward a substrate‐based approach aiming to ablate surrogate markers of the circuit during sinus rhythm in hemodynamically nontolerated and polymorphic VT. The latter approach implies an assumption that the circuits responsible for the arrhythmia are anatomical or fixed, and present during sinus rhythm. Accordingly, the lines of block delimiting the channels of the circuits are often considered fixed, although there is evidence that they are functional or more frequently a combination of fixed and functional. The electroanatomical substrate‐based approach to VT ablation performed during sinus rhythm is increasingly adopted in clinical practice and often described as scar homogenization, scar dechanneling, or core isolation. However, whether the surrogate markers of the VT circuit during sinus rhythm match the circuit during arrhythmias remains to be fully demonstrated. The myocardial scar is a heterogeneous electrophysiological milieu with complex arrhythmogenic mechanisms that potentially coexist simultaneously. Moreover, the scar consists of different areas of diverse refractoriness and conduction. It can be misleading to limit the arrhythmogenic perspective of the myocardial scar to fixed or anatomical barriers held responsible for the re‐entry circuit. Greater understanding of the role of functional lines of block in VT and the validity of the surrogate targets being ablated is necessary to further improve the technique and outcome of VT ablation.